2020
DOI: 10.3389/fcell.2020.00306
|View full text |Cite
|
Sign up to set email alerts
|

Tep1 Regulates Yki Activity in Neural Stem Cells in Drosophila Glioma Model

Abstract: Glioblastoma Multiforme (GBM) is the most common form of malignant brain tumor with poor prognosis. Amplification of Epidermal Growth Factor Receptor (EGFR), and mutations leading to activation of Phosphatidyl-Inositol-3 Kinase (PI3K) pathway are commonly associated with GBM. Using a previously published Drosophila glioma model generated by coactivation of PI3K and EGFR pathways [by downregulation of Pten and overexpression of oncogenic Ras] in glial cells, we showed that the Drosophila Tep1 gene (ortholog of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Remarkably, concerted overexpression of ras and dilp-6 induced Dpn in potentially all glial cells and more, consistently with further Dpn+ cell proliferation. Consistent with our findings, ectopic neuroblasts were also observed upon co-expression of activated ras V12 and knock-down of PTEN in glia, within glioma models in Drosophila ( Gangwani et al, 2020 ). We demonstrated that ectopic Dpn+ originated from glia, most particularly neuropile glia (midline glia and ‘Drosophila astrocytes’).…”
Section: Discussionsupporting
confidence: 90%
“…Remarkably, concerted overexpression of ras and dilp-6 induced Dpn in potentially all glial cells and more, consistently with further Dpn+ cell proliferation. Consistent with our findings, ectopic neuroblasts were also observed upon co-expression of activated ras V12 and knock-down of PTEN in glia, within glioma models in Drosophila ( Gangwani et al, 2020 ). We demonstrated that ectopic Dpn+ originated from glia, most particularly neuropile glia (midline glia and ‘Drosophila astrocytes’).…”
Section: Discussionsupporting
confidence: 90%
“…They also found that suppression of CD109 downregulated the YAP/TAZ signature and decreased the TAZ protein level in glioma stem cells. Likewise, Gangwani et al reported that the Drosophila Tep1 gene (ortholog of human CD109) regulates Yki (the Drosophila ortholog of human YAP/TAZ) using a Drosophila glioma cell model [ 29 ]. However, the molecular mechanism through which CD109 regulates YAP/TAZ was not clarified in the abovementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Here, CD109 was suggested to act upstream of the Yap/Taz signaling pathway ( Minata et al, 2019 ). In a Drosophila glioma model, it was also shown that TEP1 ( Drosophila ortholog of human CD109) regulates the Drosophila Yki pathway (ortholog to Yap/Taz) ( Gangwani et al, 2020 ). This functional consensus of TEP1 and CD109 might also favor a structural similarity between both proteins.…”
Section: Discussionmentioning
confidence: 99%